Comparative Study on the Regeneration of Fe3O4@Graphene Oxide Composites - Hu, Zhongliang; Zhang, Xiaojing; Li, Jingying; Zhu, Yirong (Frontiers in Chemistry, 2020)
In this study, two kinds of composites with the structure of graphene oxide (GO) sheets wrapped magnetic nanoparticles were investigated on their regeneration. The composites have a similar core-shell structure, but the interactions between the core and shell are quite different, which are electrostatic and covalent. They were characterized by scanning/transmission electron microscopy, power X-ray diffraction, and vibrating sample magnetometer analysis. Their morphologies and structures of the samples had been revealed using methylene blue and Pb(II) as adsorbates during regeneration. The results showed that the composites with covalent bonding interaction could maintain a stable core-shell structure and present a good regeneration performance for adsorption-desorption of methylene blue and Pb(II). The composites with electrostatic interaction could approximately preserve its core-shell structure and could be recyclable for adsorption-desorption of methylene blue, however, they would disintegrate its core-shell structure during adsorption/desorption of Pb(II), thus greatly decreasing their regeneration performance. The regeneration mechanisms of the composites were analyzed, which could provide a useful theoretical guide to design the GO sheets wrapped magnetic nanoparticles composites.